(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The paper deals with the analysis of scientists’ views concerning the term «approach». The communicative approach, its intention and advantages in the main stage of studying Ukrainian as a foreign language are accentuated.